Application of bare nanoparticle-based nanofluids in enhanced oil recovery. (1st May 2020) - Alnarabiji, Mohamad Sahban; Husein, Maen M.
Abstract: Nanofluids offer many advantages over surfactant and polymer solutions during enhanced oil recovery (EOR). This review discusses the current state and future prospects of nanofluids consisting of bare nanoparticles (NPs) in aqueous media and their application in EOR. The following topics are addressed: advantages and challenges of bare and functionalized nanofluid injection, observations on NP mobility within reservoirs as well as mechanisms pertaining to nanofluid EOR. The role of the NP chemical nature, size, size distribution, surface charge, isoelectric point and concentration is thoroughly reviewed. The impact of factors such as high temperature, pH, salinity and the nature of reservoir rock surface are highlighted in order to provide a better understanding and ability to predict EOR rate of nanofluid injection. Potential synergy among the different NP characteristics is gaged through experimental results from multiple research clusters. The proposed mechanisms; namely reduction of interfacial tension, increment in viscosity, in situ formation of Pickering emulsion and/or alteration of the disjoining pressure and wettability are critically discussed. Future work in this field should address the following gaps; (1) precise determination of the isoelectric point of the NPs under reservoir conditions; (2) workable measurement to faithfully capture particle size distribution; (3) a mean to correlate aging time of the NPs in the base fluid under reservoir environment; and (4) exploring the fine balance between surface charge needed to stabilize the particles while maintain their effectiveness as interfacial tension modifiers.